The role of intestinal macrophage polarization in colitis-associated colon cancer - Deng, Yujie; Jia, Xiaobing; Liu, Liu; He, Qiao; Liu, Lei (Frontiers in Immunology, 2025)
Chronic inflammation of the intestine is a significant risk factor in the development of colorectal cancer. The emergence of colitis and colorectal cancer is a complex, multifactorial process involving chronic inflammation, immune regulation, and tumor microenvironment remodeling. Macrophages represent one of the most prevalent cells in the colorectal cancer microenvironment and play a pivotal role in maintaining intestinal health and the development of colitis-associated colon cancer (CAC). Macrophages are activated mainly in two ways and resulted in three phenotypes: classically activated macrophages (M1), alternatively activated macrophages (M2). The most characteristic of these cells are the pro-inflammatory M1 and anti-inflammatory M2 types, which play different roles at different stages of the disease. During chronic inflammation progresses to cancer, the proportion of M2 macrophages gradually increases. The M2 macrophages secrete cytokines such as IL-10 and TGF-β, which promote angiogenesis and matrix remodeling, and create the favorable conditions for cancer cell proliferation, infiltration, and migration. Therefore, macrophage polarization has a dual effect on the progression of colitis to CAC. The combination of immunotherapy with reprogrammed macrophages and anti-tumor drugs may provide an effective means for enhancing the therapeutic effect. It may represent a promising avenue for developing novel treatments for CAC. In this review, we focus on the process of intestinal macrophage polarization in CAC and the role of intestinal macrophage polarization in the progression of colitis to colon cancer, and review the immunotherapy targets and relevant drugs targeting macrophages in CAC.